2013
DOI: 10.3402/gha.v6i0.20444
|View full text |Cite
|
Sign up to set email alerts
|

Primary healthcare providers’ views on improving sexual and reproductive healthcare for adolescents in Bolivia, Ecuador, and Nicaragua

Abstract: ObjectivesTo elicit the views of primary healthcare providers from Bolivia, Ecuador, and Nicaragua on how adolescent sexual and reproductive health (ASRH) care in their communities can be improved.MethodsOverall, 126 healthcare providers (46 from Bolivia, 39 from Ecuador, and 41 from Nicaragua) took part in this qualitative study. During a series of moderated discussions, they provided written opinions about the accessibility and appropriateness of ASRH services and suggestions for its improvement. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
3
18
0
1
Order By: Relevance
“…The incipient results regarding adolescents suggests greater involvement of the school and parents in order to optimize care. (17) The incipient result of the welcoming and the non-implementation of the Manchester protocol, indicate the need to move forward with the humanization of care. Welcoming with risk classification prioritize patients who need immediate treatment or acute conditions, reinforcing the principle of equity in the FHS, however the scientific production in Brazil is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The incipient results regarding adolescents suggests greater involvement of the school and parents in order to optimize care. (17) The incipient result of the welcoming and the non-implementation of the Manchester protocol, indicate the need to move forward with the humanization of care. Welcoming with risk classification prioritize patients who need immediate treatment or acute conditions, reinforcing the principle of equity in the FHS, however the scientific production in Brazil is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…This can also be verified through the results of a study that points out that the health professionals perceive information; the provision of contraceptive methods; the effectiveness of the method; the prompt delivery of the male condom; counseling on the repercussions of an unplanned pregnancy; sexuality detached from pregnancy; the inclusion of the sexual partner in family planning decisions; and conducting group orientation for adolescents, women and couples, as important factors for the quality of contraceptive care, but point out that the FH units are not a place for training the health professionals on issues related to sexual and reproductive health. 15 In addition to these factors, other studies add that the perceptions and knowledge of the health workers, especially the knowledge deficits of PHC workers regarding the theme of contraception, [16][17][18][19][20] by far determine the quality of care offered, example: there is the non-prescription of Emergency Contraception (EC) by some professionals, with the simple justification that the use of EC will not become a routine. 20 Also, considering the note that PHC workers make the precariousness of sexual and reproductive health care to adolescents and men, and the latter, in particular, are said to be clients who hardly seek PHC to address sexual and reproductive health issues, and the biggest perceived obstacles are misconceptions and preconceptions, especially those related to vasectomy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several studies indicate that the care for adolescents, in the context of sexual and reproductive health, is precarious and not specific, 26 some also consider that the way the professionals perceive teenage pregnancy is what will influence their attitude toward prescribing contraceptive methods for adolescents; 27 others believe that increasing adolescents' access to the health services requires a reduction in formalities, besides perceiving promoting characteristics for health actions in the school. 19 For the outcome of the scenes, there was the insertion of the proposed action chosen. With slight variations, it was observed that the efforts of the FHts to effectively perform and improve contraceptive care were aimed at ensuring the users' access to the health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, providers stated that counsellors should have the ability to communicate with adolescent in order to provide appropriate counselling services, so the counselling skills of midwives should be increased. In the study of Jarosowens too, care providers agreed with the additional training of the staff of health centers and believed that education would improve service providing and communication skills with adolescents [33].…”
Section: Discussionmentioning
confidence: 99%